EDUCATION GOUPS AT SCHOOL ABOUT DEATH: CHALLENGES AND REFLECTIONS FOR HEALTH PSYCHOLOGY - da Costa, Ana Christina S. L.; Ana Honorato, Eduardo Jorge Sant’; Lemosm, Sônia Maria; da Silva, Tirza Almeida; de Souza, Daniel Cerdeira; da Costa, Luziane Vitoriano (International Journal of Research -GRANTHAALAYAH, 2019)
This paper aims to report an experience of a group of psychologists working in the field of Health Psychology. It is the result of an intervention work in a school, located in Manaus, capital of Amazonas State, Brazil. It was an education proposal on the theme Death, aimed at children between 8 and 12 years. Children with delays in school performance were selected and their experience broadened the concept of Health and Psychology, building a more affectionate and skillful relationship in understanding the demands of others outside the established spaces of Health.